Influence of Prebending Principle Rolling Bush on Chain Performance - Liu Yi; Liu Depeng; Wang Shungong; Zhao Weiping (Jixie chuandong)
The prebending principle is used to roll the bushing,the gap of the seam can be reduced to a minimum and the fluctuation range of dimension is reduced obviously. The wear-resisting performance of the prebending bushing chain is significantly improved compare with the general bushing chain. The wear is reduced where the bushing contact with the pin,the surface hardness of the bushing is improved under the effect of cyclic hardening.